The Influence of Entrepreneurial Spirit on Students’ Entrepreneurial Motivation and Intention: A Systematic Literature Review - Rudy Makanung (www.amertainstitute.com, 2025)
Entrepreneurship has been widely recognized as a strategic instrument for addressing graduate unemployment and fostering sustainable economic development, particularly in emerging economies such as Indonesia. Despite the integration of entrepreneurship education into higher education curricula, students’ entrepreneurial motivation and intention remain relatively low. This condition highlights the importance of entrepreneurial spirit as a fundamental psychological construct shaping entrepreneurial behavior. This study aims to systematically review and synthesize existing empirical literature on the influence of entrepreneurial spirit on students’ entrepreneurial motivation and entrepreneurial intention. Employing a literature review approach, relevant studies were collected through academic databases such as Google Scholar, Mendeley, and other reputable online sources. The analysis focuses on identifying consistent patterns, dominant theoretical perspectives, and key findings related to the interrelationships among entrepreneurial spirit, motivation, and intention. The review reveals three main conclusions: (1) entrepreneurial spirit has a significant influence on entrepreneurial motivation; (2) entrepreneurial spirit directly affects students’ entrepreneurial intention; and (3) entrepreneurial motivation plays a mediating role in strengthening entrepreneurial intention. In addition, several contextual factors—such as income expectations, entrepreneurial knowledge, personal independence, family environment, and creativity—are identified as complementary determinants influencing students’ entrepreneurial motivation and intention. This study contributes theoretically by providing an integrated conceptual framework that consolidates fragmented findings in the entrepreneurship literature, particularly within the context of higher education. Practically, the findings offer insights for universities and policymakers in designing more effective entrepreneurship education programs aimed at cultivating entrepreneurial spirit and enhancing students’ motivation and intention to engage in entrepreneurial activities.